Effects of Nonuniform Incident Illumination on the Thermal Performance of a Concentrating Triple Junction Solar Cell - Fahad Al-Amri; Tapas Kumar Mallick (International Journal of Photoenergy)
A numerical heat transfer model was developed to investigate the temperature of a triple junction solar cell and the thermal characteristics of the airflow in a channel behind the solar cell assembly using nonuniform incident illumination. The effects of nonuniformity parameters, emissivity of the two channel walls, and Reynolds number were studied. The maximum solar cell temperature sharply increased in the presence of nonuniform light profiles, causing a drastic reduction in overall efficiency. This resulted in two possible solutions for solar cells to operate in optimum efficiency level: (i) adding new receiver plate with higher surface area or (ii) using forced cooling techniques to reduce the solar cell temperature. Thus, surface radiation exchanges inside the duct and Re significantly reduced the maximum solar cell temperature, but a conventional plain channel cooling system was inefficient for cooling the solar cell at medium concentrations when the system was subjected to a nonuniform light distribution. Nonuniformity of the incident light and surface radiation in the duct had negligible effects on the collected thermal energy.